PEMBERDAYAAN MASYARAKAT MELALUI JAMA'AH SHOLAWATAN - Syarifuddin Syarifuddin; Samsul Arifin (LISAN AL-HAL: Jurnal Pengembangan Pemikiran dan Kebudayaan, 2016)
At-tawazun Counseling: Pesantren Based Best Practices Counselling For Developing a better person.The characteristics of Islam Nusantara (The Islamic Archipelago) which is known as tawasuth, tasamuh, and tawazun can be found in various areas of life as it covers many aspects such as thought, movement and best practices. The characteristics of Islam NusantaraÂ are also seen in the world of psychology and counseling which have been practiced in pesantren by santri (students in pesantren) and clerics. This paper aims to; first to develop a design of psychology and counseling from the texts of classical book (kitab kuning), especially texts of morality and mysticism taught in pesantren. Second, to describe the implementation of best practices related to psychology and counseling in pesantren, especially on the formation of character psychologically so that the students (santri) grow and develop as better persons. Lastly, to understand the traces of Islam Nusantara in boarding schools (pesantren) that becomes best practices in the field of psychology and counseling.The researcher adopted several stages of Mallon (2004: 75-85) that uses quadri-hermeneutics or reflexive methodology in one of his research as this study used qualitative research methods combined with the type of ethnographic hermeneutics. The findings are there are correlations between the quality of scientific prowess and skill (shalahiyyah) and integrity (character strength). Meanwhile, in behavior modification techniques, pesantren realm balance between the physical aspects, giving ta'zir and targhib, student-teacher mutual interaction (counselor-counselee) in the technique of application and other balance values. This at-tawazun construction is in line with the characteristics of the paradigm of thinking, social attitudes, and the context of the existence of Sukorejo Islamic Boarding School.Â